Geographical sovereignty in times of crisis : the Eyjafjallajökull eruption and the international community - Einar Pétur Heiðarsson 1971- (2013)
The needed transformation of the concept of sovereignty in a globalized world has until now mostly been a topic for political scientists. This is, however, changing since the complexity, interdependencies and importance of international cooperation is becoming more self-evident. Project management and crisis management are study fields that must take notice of the transforming sovereign state system. The volcanic eruption in Eyjafjallajökull-glacier, Iceland, in 2010, raised several questions regarding state sovereignty in natural crisis situation. The eruption is used here as a crisis management case that demonstrates the globalization of the international society and the transboundary risk that follow increased systematic and technological complexity of modernity. The fact that a volcanic eruption within an self-governing island in midst of the Atlantic ocean could seriously inflict European and international air traffic was an eye opener for politicians, government, the airline industry and the public. An original conceptualization of ‘geographical sovereignty’ is introduced as a tool to explain the complex relationship between nature, the globalized international community and the sovereign state system. Hin nauðsynlega umbreyting á fullveldishugtakinu í hinum hnattvædda heimi hefur til þessa nær eingöngu verið umfjöllunarefni stjórnmálafræðinga. Þetta er hins vegar að breytast þar sem margbreytileiki, gagntengsl og mikilvægi alþjóðlegrar samvinnu verður æ augljósara. Verkefnastjórnun og krísustjórnun eru rannsóknarsvið sem þurfa að taka mið af umbreytingu kerfis fullvalda ríkja. Eldsumbrotin í Eyjafjallajökli árið 2010 vöktu upp margar spurningar varðandi fullveldi ríkisins þegar náttúruhamfarir ganga yfir. Eldgosið er notað sem dæmi til að sýna hvernig áhrif hnattvæðingar alþjóðasamfélagsins og kerfis- og tæknivæðing nútímans auka við þá áhættu sem fer þvert á landamæri hins fullvalda ríkis. Sú staðreynd að eldgos á sjálfstæðri eyju í miðju Atlantshafi gæti haft veruleg áhrif á evrópskar og alþjóðlegar ...